Squamous cell carcinoma of the dog - KALDRYMIDOU (Ε. ΚΑΛΔΡΥΜΙΔΟΥ), E.; KANAKOUDIS (Γ. ΚΑΝΑΚΟΥΔΗΣ), G.; TOLIOU (Θ. ΤΟΛΙΟΥ), Th.; POUTAHIDIS (Θ. ΠΟΥΤΑΧΙΔΗΣ), Th.; KARAGIANNOPOULOU (Μ. ΚΑΡΑΓΙΑΝΝΟΠΟΥΛΟΥ), M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Squamous cell carcinoma is the most common skin neoplasm with cellular evidence of malignancy. Neoplastic cells preserve characteristics of the stratum spinosum and infiltrate dermis. Squamous cell carcinomas classification is based on the degree of cell differentiation and tumor architecture and includes more than one categories. Immunohistochemistry is often applied in order to distinguish this carcinoma from other epithelial neoplasms. In the present study four squamous cell carcinomas of the dog were examined and classified. Three of them (2,3,4) presented low rates of differentiation so, immuhistochemical detection of cellular keratin was performed, in order to avoid confusion with other keratinizing epithelial neoplasms. Two out of the three above mentioned tumors (3,4) exhibited acantholysis and pseudogranular structures. Immunohistochemical detection of the carcinoembryonic antigen provided evidence to distinguish them from adenocarcinomas. Finally, in the fourth tumor (4) areas of diffuse cellular proliferation, without obvious keratinization, were observed. Many of these cells appeared elongated. In this case, the immunohistochemical detection of vimentin was performed in order to find out if these cells belonged to the connective tissue or to a spindle-cell squamous cell carcinoma.